Assessment of the Economic Efficiency of Long-Term Care System in the Stavropol Territory - I. I. Deren; K. A. Samofatova (Статистика и экономика)
The purpose of the study. The purpose of the article is to economically substantiate the effectiveness of a long-term care system functioning in the form of social services at home, compared with stationary social services for people with limited mobility and non-mobile citizens to determine the most optimal and profitable form of providing social services for the state.Materials and methods. The study used analytical and statistical data for the period 2019-2022 and 8 months of 2023 on the amount of funding and main items of expenditure within the framework of the implementation of the long-term care system in pilot social service organizations subordinate to the Ministry of Labor and Social Protection of the Population of the Stavropol Territory. Scientific methods: analysis of scientific literature on the research problem, tabular method, economic and mathematical analysis; methods of processing and displaying information using the Microsoft Excel software package.Results. The authors carried out a theoretical analysis of the scientific literature of domestic and foreign researchers on the problem of the study. The article has developed and tested the author’s methodology for assessing the economic efficiency of the system of long-term care for elderly and disabled citizens, and also presents the results of a study of this assessment on the example of the Stavropol Territory.Conclusion. The conclusions obtained based on the results of the study indicate the development of a long-term care system, the implementation of which is a priority socially significant direction at the federal and regional levels. The calculations carried out confirmed that the cost of servicing the socially vulnerable category of elderly citizens at home is lower than in the conditions of their stay in inpatient institutions. The practical significance of the study lies in the possibility of applying the results obtained in the field of management of the development of the regional public sector in the sphere of social services and systematization of the data obtained. The options proposed by the authors for calculating the amount of funding and expenses within the framework of the system of long-term care for the disabled and older people can significantly affect economic growth, changes in the conditions and remuneration of personnel involved in the provision of services, the formation of gross domestic product.